2020
DOI: 10.1016/j.gaitpost.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Minimum toe clearance and tripping probability in people with unilateral transtibial amputation walking on ramps with different prosthetic designs

Abstract: Background: Minimum Toe Clearance (MTC) is defined as the minimum vertical distance between the lowest point under the front part of the foot and the ground, during mid-swing. Low values of MTC and walking on inclines are both related to higher probability of tripping and falling in lower limb amputees. New prosthetic designs aim at improving MTC, especially on ramps, however the real effect on MTC still needs investigation. The objective of this study was then to evaluate the effect of different prosthetic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…People with transfemoral amputation fall more frequently than the transtibial amputees, with more than 60% of falls at least once in a year due to tripping [2], [3]. Tripping occurs during the mid-swing phase of gait when the toe approaches minimum distance from the ground, i.e., at minimum toe clearance (mTC) which is defined as the minimum vertical distance between the lowest point under the front part of the foot and the ground, during midswing, while the foot progresses forward with maximum swing velocity [4], [5]. Therefore, mTC is an important consideration to quantify the risk of tripping in the lower limb amputee population.…”
Section: Introductionmentioning
confidence: 99%
“…People with transfemoral amputation fall more frequently than the transtibial amputees, with more than 60% of falls at least once in a year due to tripping [2], [3]. Tripping occurs during the mid-swing phase of gait when the toe approaches minimum distance from the ground, i.e., at minimum toe clearance (mTC) which is defined as the minimum vertical distance between the lowest point under the front part of the foot and the ground, during midswing, while the foot progresses forward with maximum swing velocity [4], [5]. Therefore, mTC is an important consideration to quantify the risk of tripping in the lower limb amputee population.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in time may also explain the apparently higher MFC, as a higher clearance may be possible with a longer step time. Therefore, we may conclude that the increased swing and step times may be related to a slower limb translation rather than achieving significantly higher distances with the RL, or may even be related to the counteracting of some instability caused by the AFO [ 29 ]. This agrees with Vistamehr et al [ 30 ], who observed a decrease in the propulsive impulse in the AFO limb compared to the contralateral leg.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, below knee prosthesis users are likely to be fitted with a hydraulic ankle but, once more, because the data were not recorded, the proportion of users in this dataset is unknown. There is published evidence that hydraulic ankles present increased ground clearance during swing [27,28] and enhanced standing stability [29], compared to feet that are rigidly-attached at the ankle. More recently, some researchers have investigated how the combinations of advanced prosthetic knees and ankles work together, suggesting the combination of the two technologies may have biomechanical advantages for balance [29], mobility [30] and navigating everyday, environmental barriers, such as stairs and slopes [30].…”
Section: Limitationsmentioning
confidence: 99%